Space Manufacturing Facilities 1975
DOI: 10.2514/6.1975-2041
|View full text |Cite
|
Sign up to set email alerts
|

The Colonization of Space

Abstract: Write a 250+ word response to the article. (If you are a teacher or student who would like to modify this Google Doc, go to File > Make a Copy. I cannot and do not respond to Share requests-my apologies!) The Colonization of Space By The Week Staff, 11-26-18 Humanity is inching closer to establishing colonies on other worlds. Is it really feasible? Here's everything you need to know: What's the timeline? The best guess is that humanity will set up shop on the moon or Mars or both sometime in the 2030s. NASA sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…In the future, asteroids may be used as resources for space colonization (O'Neill, 1974;O'Leary, 1977;Lewis, 1993). Carbonaceous chondrite materials from Phobos and Deimos may be used as fertilizers in Martian terraforming (Lewis, 1997).…”
Section: Terraforming and Space Colonizationmentioning
confidence: 99%
“…In the future, asteroids may be used as resources for space colonization (O'Neill, 1974;O'Leary, 1977;Lewis, 1993). Carbonaceous chondrite materials from Phobos and Deimos may be used as fertilizers in Martian terraforming (Lewis, 1997).…”
Section: Terraforming and Space Colonizationmentioning
confidence: 99%
“…The preceding sections demonstrated bioresources in asteroids materials, that can be used as soils for agriculture, or as extracts for hydroponics. (O'Neill, 1974, Sagan, 1994Ming and Henninger, 1989;Lewis, 1993) The potential yield of biomass can be calculated from the compositions of the resource materials, compared with the requirements of biological tissues.…”
Section: Potential Biomassmentioning
confidence: 99%
“…Human expansion in the Solar System has been contemplated for over a century since Tsiolkovsky, and it is a long-term goal of NASA ( (Rynin, 1971;O'Neill, 1974O'Neill, , 1977McKay et al, 1991;Sagan, 1994, O'Keefe, 2002Griffin, 2014). Astroecology experiments with carbonaceous meteorites showed that microorganisms, plant cultures and shrimp hatchlings can grow on these materials (Mautner 2002a, b) Therefore biological materials for space-based ecosystems and human populations can be derived from these in-situ asteroid resources (Mautner, 2002a,b, Montague et al, 2012, similarly to in situ resource utilization (ISRU) for industrial and structural materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liaison holds great potential for propelling space shuttle craft into orbit with an essentially infinite specific impulse, especially considering that MHD thrusters are known for their ability to produce the very high exhaust velocities required for realistic air-breathing propulsion at high altitudes. 52 " 54 The scheme becomes even more attractive when it is realized that higher propulsive efficiencies may allow a single orbital laser power station, perhaps attached to a space laboratory or colony, 55 to supply only several gigawatts of power. On a close fly-by orbit, radiant energy would be transmitted to the planetary surface, the shuttle craft "beamed-up," and docking in orbit would occur several thousand miles downrange.…”
Section: Introductionmentioning
confidence: 99%